Exploration of risk factors and characteristics of COVID-19 infection among patients with hematological malignancies in Suzhou, China: a retrospective study - Yao, Yao; Di, Wenjuan; He, Fangkai; Liu, Bin; Chen, Xue; Guan, Xiaojun; Huang, Zhou; Wang, Ying; Wu, Depei (Frontiers in Oncology, 2025)
Background and aimPatients diagnosed with cancer, particularly those with hematologic malignancies, frequently exhibit a state of immunosuppression. Currently, there remains a scarcity of dependable biomarkers for assessing the severity of COVID-19 in individuals with hematologic malignancies. We conducted a retrospective study of morbidity and mortality in patients with hematological malignancies (HM) who had contracted COVID-19. The aim was to offer a reference for clinical diagnosis and treatment.MethodsA total of 71 patients with HM-confirmed COVID-19 were enrolled from December 2022 to May 2023. Clinical symptoms, laboratory findings, and treatment approaches were collected and documented. Patients were classified into survival and death groups based on their COVID-19 outcomes, and statistical analysis was performed on the clinical data from both groups.ResultsAmong the 71 patients, 57 (80.3%) were alive, and 14 (19.7%) had died. The mean age of patients in the death group was significantly higher than that of the survival group (51.29 ± 20.76 vs. 49.47 ± 13.04, P=0.030). The proportion of patients receiving mechanical ventilation was significantly higher in the death group (P<0.001). The mortality rate was significantly higher in the critically severe group compared to the mild, moderate, and severe groups (P<0.001). Correlation analysis revealed that certain laboratory indicators lactic acid dehydrogenase (LDH), albumin (ALB), creatine kinase (CK), troponin T (TnT), N-terminal pro-brain natriuretic peptide (NT-proBNP) and fibrin degradation product (FDP), which exhibited significant differences between groups, were significantly correlated with COVID-19-related mortality (all P<0.05). The Cox proportional hazards model indicated that LDH was an independent risk factor associated with the prognosis of HM-confirmed COVID-19.ConclusionPatients with hematologic malignancies suffer severe morbidity and mortality due to COVID-19 infection. LDH may serve as a risk factor associated with prognosis in the treatment of COVID-19. Monitoring variations in LDH levels can assist healthcare providers in evaluating disease progression, adjusting treatment plans in a timely manner, and predicting patient outcomes.